Assessing the Local Tourism Infrastructure and Services towards Tourism Development of San Jose - Ariane Pesimo Abundabar; Marilou A. Pongpong (International Journal of Applied Research in Tourism and Hospitality, 2022)
Local tourism planning and development is a complex area of concern. Many local destinations initiate tourism programs to achieve economic, social, and environmental sustainability. Thus, the local government must explore either its potential natural resource or its potential human resource, including the tourism sector towards development. This study focused on assessing the local tourism infrastructure and services for tourism development in San Jose, Camarines Sur. The study employed the Community-Based Participatory Action Research (CBPAR) and Exploratory-Descriptive Research Methods (EDRM). These methods involved local stakeholders in assessing infrastructure and services through public meetings, workshops, and individual consultations. The conducted assessments aided the identification of the significant impacts and opportunities in the study area. The study revealed that though the primary services are present in the area, specific issues and challenges must be addressed to improve these services and cater to visitor needs. Thus, the identified problems and challenges on infrastructure must be addressed since the infrastructure is essential for tourism initiatives to prosper.